This research is conducted with a purpose to find out the influence of profitability, efficiency, and syariah compliance to the yield sukuk mudharabah. Variables which are used in this research are profitability, efficiency, and syariah compliance as inde - Ernawati, Ernawati; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is conducted with a purpose to find out the influence of profitability, efficiency, and syariah compliance to the yield sukuk mudharabah. Variables which are used in this research are profitability, efficiency, and syariah compliance as independent variables, and yield sukuk mudharabah as the dependent variable. The annual data of 2008-2012 periods is used as the source of data. The sample of the research consists of three issuers of sukuk mudharabah from the total of five issuers of sukuk mudharabah which are listed in Indonesia Stock Exchange (IDX) and they have been chosen by using purposive sampling. Quantitative method is the statistic method that is used in this research and multiple linear regressions as test instrument. The normality assumption test shows that the data has normally distributed. The autocorrelation assumption test shows that the data is used randomly, so there is no problem with the autocorrelation. The multicolinearity assumption test shows that there is no correlation among variables in the independent variables so the multicolinearity does not become any serious problem. The heteroscedasticity assumption test shows that the variant of constant disturbance probability distribution for the whole observation on the independent variables or in the other words heteroscedasticity does not become any problem. The result of the research shows that profitability test does not have any influence to the yield sukuk mudharabah, the efficiency variable has positive influence to the yield sukuk mudharabah, and the syariah compliance variable does not have any influence to the sukuk mudharabah in Indonesia. Keywords: Profitability, Efficiency, Syariah Compliance, Yield Sukuk Mudharabah.